Influence of Selenium and Manganese Nanoparticles Prepared by Laser Induced Plasma on Levels of the Thyroid Gland (T3, T4 and TSH) - Jassim, Rafal H.; Aadim, Kadhim A. (International Journal of Psychosocial Rehabilitation, 2020)
In this study, thin films were prepared by laser induced plasma (LIP) method using a pulsed laser (Nd: YAG) of wavelength (1064nm) at the temperature of the room and in the vacuum and the effect of different energies (650 mJ-950 mJ) to study the structural and structural properties (XRD, AFM). Similarly, selenium and manganese nanoparticles were manufactured by laser-induced plasma and also using pulsed lasers upon collision with solid target atoms. The effect of these nanomaterials on levels of the thyroid gland (T3, T4 and TSH) was observed under two doses of each component (1mg/kg, 4mg/kg).The relative weight of mice was observed for each group and the effect of selenium nanomaterials than manganese nanomaterial was affected on the weight of rats, i.e. on the metabolism process.It turns out that selenium nanomaterial is the most influencing metabolism and weight of manganese nanoparticles.